2020
DOI: 10.1097/bco.0000000000000863
|View full text |Cite
|
Sign up to set email alerts
|

Combined medial malleoplasty and Taylor Spatial Frame after a supramalleolar osteotomy in the treatment of ankle deformity in skeletally immature patients: A prospective study of a novel technique and the short-term results

Abstract: Background: This study examined the effectiveness of the Taylor Spatial Frame (TSF) in the treatment of deformity and limb shortening caused by distal tibial physeal arrest and the effectiveness in maintaining alignment and stability by reconstruction of the medial malleolus and the medial collateral ligament using an autogenous iliac crest graft and attached sartorius muscle-tendon. Methods: Thirteen pediatric patients with angular deformity of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…6 The use of the Taylor Spatial Frame (TSF) allows six axes of deformity correction and utilizes computer software and virtual hinges that allow accurate deformity correction. [7][8][9] Although the use of TSF is popular, there are only a few studies that have reported the results of rotational deformity correction, especially in skeletally immature patients. The aim of this study was to evaluate the effectiveness of the TSF as a primary tool in the treatment of severe rotational deformities of lower limbs that were caused by neglected malunited femoral fractures in pediatric and adolescent patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The use of the Taylor Spatial Frame (TSF) allows six axes of deformity correction and utilizes computer software and virtual hinges that allow accurate deformity correction. [7][8][9] Although the use of TSF is popular, there are only a few studies that have reported the results of rotational deformity correction, especially in skeletally immature patients. The aim of this study was to evaluate the effectiveness of the TSF as a primary tool in the treatment of severe rotational deformities of lower limbs that were caused by neglected malunited femoral fractures in pediatric and adolescent patients.…”
Section: Introductionmentioning
confidence: 99%
“…The correction of complex deformities with the Ilizarov frame requires a long learning curve, and correction of rotational deformities is a complex task requiring frequent modifications and adjustments of the frame during the correction process 6. The use of the Taylor Spatial Frame (TSF) allows six axes of deformity correction and utilizes computer software and virtual hinges that allow accurate deformity correction 7–9…”
Section: Introductionmentioning
confidence: 99%